2014
DOI: 10.1002/dta.1629
|View full text |Cite
|
Sign up to set email alerts
|

Is urine an alternative to cosmetically treated hair for the detection of drugs and alcohol?

Abstract: This study attempts to assess the utility of the urine matrix as an alternative to cosmetically treated hair for the detection of drugs and alcohol for driving licence re-granting in 1026 cosmetically treated hair samples and 33 262 urine routine samples. No significant difference was observed between the percentage positive samples in cosmetically treated hair to those in urine at both the 95% and 99% significance level for amphetamines, cocaine, opiates, benzodiazepines, and methadone. Significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Based on the observed facts that (1) no significant difference in the positivity rate was observed between treated and non‐treated hair for both drugs and EtG tested for abstinence at the MPA cut‐offs and that (2) significant changes in drug concentrations in hair were observed only at high drug concentrations (corresponding to 20 times the MPA cut‐off and 95th percentiles or higher in the population studied), it can be concluded that dyed or bleached hair is not automatically useless for drug and EtG detection; conversely, hair analysis is a powerful tool, often the only means to detect retrospective drugs and/or alcohol consumption even in dyed or bleached hair. Consequently, guidelines considering the exclusion of dyed or bleached hair shall be reviewed, especially because it has been shown that urine is a worse alternative to coloured hair for the detection of drugs of abuse and especially EtG as required for the driving license re‐granting programme MPA in Germany …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the observed facts that (1) no significant difference in the positivity rate was observed between treated and non‐treated hair for both drugs and EtG tested for abstinence at the MPA cut‐offs and that (2) significant changes in drug concentrations in hair were observed only at high drug concentrations (corresponding to 20 times the MPA cut‐off and 95th percentiles or higher in the population studied), it can be concluded that dyed or bleached hair is not automatically useless for drug and EtG detection; conversely, hair analysis is a powerful tool, often the only means to detect retrospective drugs and/or alcohol consumption even in dyed or bleached hair. Consequently, guidelines considering the exclusion of dyed or bleached hair shall be reviewed, especially because it has been shown that urine is a worse alternative to coloured hair for the detection of drugs of abuse and especially EtG as required for the driving license re‐granting programme MPA in Germany …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, guidelines considering the exclusion of dyed or bleached hair shall be reviewed, especially because it has been shown that urine is a worse R. Agius alternative to coloured hair for the detection of drugs of abuse and especially EtG as required for the driving license re-granting programme MPA in Germany. [37] Further research is needed to:…”
Section: Resultsmentioning
confidence: 99%
“…In a similar in vitro study a decrease of EtG by, as a mean, 73.5% was found after bleaching whereas incubation of EtG alone with H 2 O 2 (15%) led only to a decomposition of 45% [88]. But, this statistics has to be seen with caution since false-negative results are not included (portion of positive results in cosmetically treated samples was only 4.1% [91] as compared to 21% and 12.7% [92,93] in the same whole clientele). Contrary to that, no effect on dyeing was reported in another statistic study [90].…”
Section: Effect Of Hair Color Hair Care and Cosmetic Treatmentmentioning
confidence: 99%
“…Therefore, it is a common tenor of these comparative studies that CDT and PEt as well as the nonexpensive traditional alcohol biomarkers continue to have practical importance. To a lower extent, the advantage of hair was still true for cosmetically treated hair with a positive rate of 4.09% versus 2.08% in urine [91]. In Germany, the candidates can demonstrate 1 year abstinence either by six random (24 hours' notice) urine tests in 12 months or by four separate 3 cm long hair strands collected every 3 months (EtG cutoffs 0.1 mg/L in urine and 7 pg/mg in hair).…”
Section: Comparison Of Etg and Faee In Hair With Other Alcohol Markersmentioning
confidence: 99%
“…Benzodiazepine detection in urine is a common routine test in clinical and forensic laboratories. They are monitored in cases of suspected drug-facilitated sexual assault [ 4 , 5 , 6 , 7 , 8 , 9 ], in workplace contexts [ 9 , 10 , 11 ], in suspected impaired drivers [ 12 , 13 , 14 , 15 , 16 ], and in cases of suspected intoxication [ 17 , 18 , 19 ]. Hence, the laboratories need a sensitive immunoassay for use as a screening procedure.…”
Section: Introductionmentioning
confidence: 99%